Aortic valve-sparing root replacement with Tirone E. David's reimplantation technique: single-centre 25-year experience. (29th March 2021) - Beckmann, Erik; Martens, Andreas; Krüger, Heike; Korte, Wilhelm; Kaufeld, Tim; Stettinger, Alissa; Haverich, Axel; Shrestha, Malakh Lal
Abstract: : OBJECTIVES: Tirone E. David described aortic valve-sparing root reimplantion (AVSRR) almost 30 years ago. At our centre, we adopted this operation in 1993, and since then, we have performed >700 operations over a time period of >25 years. In this report, we present our single-centre experience. METHODS: Between 1993 and 2019, a total of 732 patients underwent AVSRR at our centre. The mean age was 53 ± 15 and 522 (71%) were male. Marfan syndrome was present in 117 (16%) patients and bicuspid aortic valve in 81 (11%). The indication for surgery was aortic root aneurysm in 588 (80%) patients and acute aortic dissection in 144 (20%) patients. RESULTS: Mini-sternotomy was performed in 74 (10%) patients. A straight tube graft (David I) was used in 677 (92%) and a Valsalva-graft in 55 (8%) patients. Cusp plasty was done in 83 (11%) patients. Concomitant cardiac procedures were performed in 438 (60%) patients. Overall in-hospital mortality was 3.8% ( n = 29) and 1.9% ( n = 11) in elective cases. Postoperative echocardiography was available for 671 patients and showed aortic insufficiency (AI) ≤I° in 647 (96%) patients. The mean follow-up time was 10 ± 6.7 years and comprised a total of 7307 patient-years. The 1-, 5-, 10- and 15-year survival rates were: 93%, 88%, 77% and 65%, respectively. The rates for freedom from valve-related reoperation at 1, 5, 10 and 15 years after initial surgery were 97%, 93%, 88% and 85%, respectively. Cox regression analysis identified age [odds ratio (OR) = 0.975, 95% confidence interval (CI) = 0.955–0.995, P = 0.016], hyperlipidaemia (OR = 1.980, 95% CI = 1.175–3.335, P = 0.010), preoperative level of left ventricular ejection function (OR = 1.749, 95% CI = 1.024–2.987, P = 0.041) and postoperative degree of AI (OR = 1.880, 95% CI = 1.532–2.308, P ≤ 0.001) as risk factors for the future AI or reoperation. CONCLUSIONS: David procedure can be performed extremely safely, with low risks for perioperative morbidity and mortality, both in elective situations via minimally invasive access and in emergent settings for acute aortic type A dissection. Regarding long-term outcome, David's AVSRR seems to provide excellent clinical results and sustainable function of the aortic valve in the majority of patients almost 3 decades after its introduction.